Tackling Income Inequality: What Works and Why? - Cuesta, Jose; Negre, Mario; Revenga, Ana; Schmidt, Maika (Journal of Income Distribution®, 2018)
This article reviews the most recent and relevant evidence on key domestic policy interventions that are effective in reducing income inequality in developing countries, the benefits they generate, the choices that need to be made regarding their design and implementation, and the trade-offs that are associated with them. It focuses on a few policy areas in which there is a sufficient body of rigorous evidence to draw useful lessons with confidence: early childhood development, including breastfeeding; universal health care; good-quality education; conditional cash transfers; Investments in rural infrastructure; and taxation. The review concludes that there are many pathways to reducing inequality, from narrowing gaps in income generation opportunities to narrowing the potential for inequalities in human capital development before the inequalities emerge, smoothing consumption among the most deprived, and Redistribution in favor of the poor. Many interventions are simultaneously associated with equalizing outcomes, improved competition, and economic efficiency. Good interventions combining equality promotion and efficiency are possible in all settings and at different times; this includes interventions disproportionately benefiting the poorest in low-income countries during periods of crisis. Despite the significant increase in knowledge about equality interventions, the article makes a strong call for more microeconomic data and better—more precise—analysis to evaluate the effectiveness of interventions.